On luminescence stimulated from deep traps using thermally-assisted time-resolved optical stimulation in α-Al2O3:C. (July 2016) - Nyirenda, A.N.; Chithambo, M.L.; Polymeris, G.S.
Abstract: We report a study of charge transfer mechanisms of electrons stimulated optically from very deep traps, also known as donor traps, in α-Al2 O3 :C. The investigations were carried out using thermally-assisted time-resolved optical stimulation, thermoluminescence and by way of residual thermoluminescence from the main electron trap. When the charges are optically stimulated from the deep traps, they are redistributed via the conduction band to the main electron trap and the shallow trap from where they are optically or thermally released for recombination at luminescence centres. The luminescence is strongly quenched at high measurement temperature as evident by very short luminescence lifetimes at these temperatures. The main peak due to residual thermoluminescence is located at a higher temperature than the conventional main peak. Highlights: The transfer mechanisms of electrons from deep traps in cα-Al2 O3 :C is reported. Electrons from deep traps are redistributed to the main and shallow trap before recombination. The luminescence from deep traps is affected by thermal quenching showing that the F-centre is key in the process. W = 1.028 ± 0.002 eV and ν =   2.8 × 10 13  s −1 .